TRANSFORMATION OF ‘MOOIE INDIË’ VISUAL DISCOURSE THROUGH RADEN SALEH’S PAINTING ‘MERAPI, ERUPTION BY DAY’ - Krisnambudi, Dionisius; Habsari, Sri Kusumo; Farhah, Eva (Universitas Gadjah Mada, 2026)
This study examines the transformation of the “beautiful Indies” (mooie Indië) visual discourse through Raden Saleh’s painting “Merapi, Eruption by Day”. The “beautiful Indies” style celebrated an idealized vision of the Dutch East Indies, raising questions about the influence of late-romantic European on Indigenous artists such as Raden Saleh. The research employs a qualitative and interpretive design grounded in Pierre Bourdieu’s theory of structuration. This framework enables a deconstruction of colonial aesthetic orders and the dynamics of symbolic power embedded in the ‘mooie Indië’ tradition. Methodologically, the study integrates heuristic and source criticism to contextualize colonial discourse, and montage analysis to reinterpret art elements of Raden Saleh’s painting, thereby exposing tensions between colonial ideology and artistic agency. Findings reveal that “Merapi, Eruption by Day” both appropriates and subverts the ‘mooie Indië’ aesthetic. Through the lens of Pierre Bourdieu, the painting demonstrates how Raden Saleh’s artistic practice can negotiates structures of domination while asserting symbolic capital for the colonized subject. At the same time, the Mount Merapi motif embodies the romantic sublime, destabilizing orientalist expectations of harmony and exotic natural beauty. Raden Saleh’s work thus transforms the colonial discourse of “the beautiful Indies” into a site of symbolic struggle, where visual strategies articulate resistance and intellectual agency within the colonial field of power.